Abies religiosa Seedling Limitations for Passive Restoration Practices at the Monarch Butterfly Biosphere Reserve in Mexico - Guzmán-Aguilar, Gerardo; Carbajal-Navarro, Aglaen; Sáenz-Romero, Cuauhtémoc; Herrerías-Diego, Yvonne; López-Toledo, Leonel; Blanco-García, Arnulfo (Frontiers in Ecology and Evolution, 2020)
To recover the structure and functionality of a deforested ecosystem, two strategies of ecological restoration are considered: active restoration, which eliminates the disturbance agents and implements strategies to accelerate site recovery, and passive restoration, which eliminates disturbance agents, allowing natural regeneration to occur. Prior to choosing passive restoration, a field evaluation of the potential for natural regeneration is important. In this context, seedling and sapling density as well as patterns of recruitment and survival are appropriate indicators of restoration potential. In the present study, we deduced the potential of sacred fir (Abies religiosa) forest of the Monarch Butterfly Biosphere Reserve to recover by natural regeneration through seedling and sapling density and mortality, since A. religiosa is the dominant tree species in wintering sites of monarch butterfly. In 2015, we evaluated seedling density in 53 sites along an elevational gradient (3050-3550 m above sea level; m a.s.l.). There was a higher density of seedlings and saplings established in canopy gaps, compared to sites under dense forest canopy. Seedling recruitment was higher in sites at intermediate elevations (3050 to 3300 m a.s.l.) than in those at higher elevations. In a second survey, we studied A. religiosa seedling mortality over the dry season of 2016 to identify the environmental variables that cause the high seedling mortality and very low recruitment. Recently emerged seedling mortality was 49.2% at the end of the dry season (June 2016). The highest monthly mortality (14.3%) was recorded in April, a dry and warm month with the lowest values of moss thickness and soil moisture. We found no negative effects of moss layer on seedling mortality; indeed, moss appears to slow soil moisture reduction at the critical end of the warm and dry season. Soil and moss moisture values in April seem to be a critical factor for A. religiosa seedling recruitment, and we expect this condition will deteriorate under projected climatic change scenarios. Thus, the potential of MBBR A. religiosa forest to recover by passive restoration is highly constrained and will require management actions to achieve successful restoration outcomes.